PENINGKATAN KOMPETENSI PEDAGOGIK GURU DALAM HASIL BELAJAR SISWA MELALUI SUPERVISI PEMBELAJARAN DI SMP SUNGAI RAYA - Mulyono, Mulyono (Universitas Tanjungpura, 2021)
Abstract Carrying out supervision activities to improve learning is one of the duties of a school principal. For the implementation to run effectively, it requires a technical skill that must be possessed by a school principal. These skills include the ability to apply appropriate supervision techniques in the implementation of supervision activities. Understanding and mastery of these techniques by the principal as a supervisor is a must if you want the implementation of supervision in schools to run well so that it can improve the quality of learning. The purpose of this school action research is to find out to what extent the coaching of the principal through the supervision of learning can improve teacher pedagogical competence on student learning outcomes. This school action research was carried out in 2 cycles, from the results of the actions taken were proven to increase teacher pedagogical competence on student learning outcomes, namely from 65% in cycle 1, increasing to 99% in cycle 2. In other words, the supervision of learning carried out by researchers as the principal can improve the pedagogical competence of teachers on student learning outcomes. Keywords: Teacher Pedagogic Competence, Student Learning Outcomes, Learning Supervision